EMPLOYEE PERFORMANCE IS REVIEWED FROM INCENTIVE, PROMOTIONS JABATAN AND EMPLOYEE WORK DISCIPLINE AT CV. BINTANG MITRA MULYA SURAKARTA - Veronika Veronika; Eny Kustiyah; Fithri Setya Marwati; Sri Hartono (JURNAL ILMIAH EDUNOMIKA, 2024)
The domestic textile market and exports abroad have been eroded by manufacturers from other countries in recent years. The threat of a decline in the industry due to the trade war that occurred and also the industry was under heavy pressure due to the impact of the corona pandemic. This study aims to examine the Incentive, Promotion Jabatan, And Work Discipline on the performance of employees of CV.Bintang Mitra Mulya Surakarta The date used in this journal are observation, interviews, distribution of questionnaires and documentation to employees of CV. Bintang Mitra Mulya The research sample was purposive sampling as many as 75 employee with multiple linear regression method. The data analysis techniques in this study included several compilation data, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, Goodness Of Fit Model multiple linear regression, f test, t test and determination test. The results showed that Incentive, Promotion Jabatan, And Work Discipline had a significant effect on the performance of CV. Bintang Mitra Mulya Surakarta. employee performance of CV.Bintang Mitra Mulya Surakarta can be explained by the variables of incentive, promotin jabatan, and work dicipline by 40.4% and others are influenced by other variables. Keywords: Incentive, Promotion Jabatan, And Work Discipline